Using core components in process evaluation: Passport skills for life - Melek Alemdar; Pamela Qualter; Michael Wigelsworth; Annie O’Brien; Suzanne Hamilton; Neil Humphrey (PLoS ONE, 2026)
Although school-based SEL programmes show robust effects in controlled studies, their real-world impact varies due to inconsistent implementation. Core components (CCs), the essential theory or evidence-based elements required to reliably produce intended effects, offer a framework to address this gap. A CC-informed approach can shift evaluation from whether a programme was delivered to how its active ingredients functioned in context and how well. We conducted a two-phase qualitative process evaluation of Passport: Skills for Life, integrating top-down and bottom-up evidence. Phase 1 involved systematic analysis of manuals, lesson plans, and resources to distil practice and instructional CCs. Phase 2 examined enactment via non-participant observations (n = 12) and semi-structured teacher interviews (n = 9) across four primary schools in North-West England. Data were analysed using deductive content and thematic analyses. We identified five practice and seven instructional CCs. Core practices—coping, self-awareness, and social awareness—were typically delivered, whereas more complex interpersonal skills (help-seeking/giving, relationship skills) were seldom observed. Instructionally, low-intensity formats (didactic talk, whole-class discussion, short written tasks) predominated, while high-engagement activities (role-plays, situation cards, Dragon’s Path) were often truncated or omitted. Delivery quality varied: facilitation sometimes built conceptual understanding, competence-building promoted rehearsal and modelling, yet disengaged practices weakened socio-emotional norms. Teacher warmth, responsiveness, and emotional literacy were pivotal; when present, SEL activities reinforced prosocial behaviours, but when absent, delivery narrowed to surface-level coverage. By linking programme theory with classroom enactment, this study shows how a CC-informed lens can reveal fidelity and quality of delivery patterns, offering a theory-aligned framework for scaling and sustaining school-based SEL.